Racetrack - Wiseman, Frederick; Davey, John (Frederick Wiseman - Intégrale Vol. 2: 1980-1994, 2016)
"Racetrack" is about the Belmont Race Track, one of the world's leading race tracks for thoroughbred racing. The film highlights the training, maintaining and racing of thoroughbred horses. Everyday occurrences are shown: in the backstretch - the grooming, feeding, shoeing, and caring for horses and the preparation for races; at the practice track the various aspects of training, exercising, and timing the horses; at the paddock - the pre-race presentation of the horses; and in the grandstand - betting and watching the races. The film also has sequences showing the variety of work done by trainers, jockeys, jockey agents, grooms, hot walkers, stable hands, and veterinarians. [www.zipporah.com]